2009
DOI: 10.1097/tp.0b013e3181b75374
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria-Reducing Effects of Tonsillectomy Alone in IgA Nephropathy Recurring After Kidney Transplantation

Abstract: These results suggest that in patients receiving oral immunosuppressive therapy for recurrence of IgA nephropathy after the kidney transplantation, reduction of the urinary protein excretion can be expected with tonsillectomy alone, without accompanying pulsed steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 17 publications
0
40
1
Order By: Relevance
“…Steroid-pulse therapy can affect downstream of the immunological mechanism by suppressing the abnormal immune response in bone marrow, leading to subsequent inflammation in renal glomeruli [11]. In recurrent IgA nephropathy, some reports demonstrated that tonsillectomy alone could be an effective treatment [12,13]. Maintenance of a regimen containing steroid after renal transplantation may contribute to reducing downstream inflammation signals and immune complex deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid-pulse therapy can affect downstream of the immunological mechanism by suppressing the abnormal immune response in bone marrow, leading to subsequent inflammation in renal glomeruli [11]. In recurrent IgA nephropathy, some reports demonstrated that tonsillectomy alone could be an effective treatment [12,13]. Maintenance of a regimen containing steroid after renal transplantation may contribute to reducing downstream inflammation signals and immune complex deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of a regimen containing steroid after renal transplantation may contribute to reducing downstream inflammation signals and immune complex deposition. The effect of tonsillectomy was reported to be especially marked in the patients with mild mesangial changes, such as minor glomerular abnormalities when compared to patients with severe mesangial changes [12]. Akagi et al [14] proposed that tonsillectomy is indicated for patients who have renal pathology scores of HG 1 to HG 3 and a serum creatinine level of 2.0 mg/dL or less.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 16 and 12 patients with or without tonsillectomy during a mean follow-up period of 60 months, proteinuria decreased significantly in all tonsillectomized patients but did not in no tonsillectomy patients. No significant differences were observed in the degree of hematuria and eGFR between the groups [14]. In other study, Ushigome et al analyzed four transplant recipients with IgAN recurrence who underwent tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to confirm any changes pathologically using protocol graft biopsies. However, several previous studies [14][15][16]20] did not perform long-term evaluations using protocol graft biopsies. We can also evaluate rejection according to the Banff classification and aggravation of the IgAN process for long-term observation about 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…A Kaplan-Meier analysis showed that the renal survival rate of the tonsillectomy group was significantly higher than in the non-tonsillectomy group, and a Cox regression analysis showed that the relative risk of terminal renal failure in the tonsillectomy group was lower than in the non-tonsillectomy group. Kennoki et al (2009) reported that in patients receiving oral immunosuppressive therapy for recurrence of IgAN after kidney transplantation, reducing of urinary protein excretion can be expected with tonsillectomy alone, without accompanying pulse steroid therapy. Wang et al (2010) recently published a meta-analysis of the clinical remission rates and long-term efficacy of tonsillectomy in IgAN patients.…”
Section: Tonsils Of Igan Patientsmentioning
confidence: 99%